Analysis of Determinants of Income Shocks During the Pandemic Period in Deli Serdang Regency, North Sumatra Province - Diwayana Putri Nasution; Ahmad Fadlan; Dewi Mahrani Rangkuty; Prasetio Prasetio (Proceeding International Pelita Bangsa, 2023)
The Covid-19 pandemic that hit Indonesia, especially in Deli Serdang Regency, gave pressure on market participants, in particular MSME traders. Many merchants were affected by impact restrictions consequence of the shortened Covid-19 pandemic time effort and impacted income. Research Objectives This is to analyze the influence of location effort and price sales to shock MSME income in Deli Serdang Regency. In research, this used a questionnaire with a Likert scale as a method of data collection. The research sample is income MSME traders in Deli Serdang Regency, namely 50 income street vendors in Deli Serdang Regency. The data analysis technique used in the study is an analysis of multiple linear regression. Research results This show that location effort and price sell influential and significant to income MSME traders in Deli Serdang Regency.